2004
DOI: 10.1023/b:phot.0000040581.94641.ed
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Gas Exchange and Water Relations in Polylepis tarapacana at Extreme Altitudes in the Bolivian Andes

Abstract: Stress-induced restrictions to carbon balance, growth, and reproduction are the causes of tree-line formation at a global scale. We studied gas exchange and water relations of Polylepis tarapacana in the field, considering the possible effects of water stress limitations imposed on net photosynthetic rate (P N ). Daily courses of microclimatic variables, gas exchange, and leaf water potential were measured in both dry-cold and wet-warm seasons at an altitude of 4 300 m. Marked differences in environmental cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…Despite P. tarapacana possesses anatomical and physiological adaptations to tolerate and minimize frost damage, temperature constitutes a limiting factor because it affects many different processes involved in plant growth. Low soil temperatures can negatively influence root growth and nutrient uptake while low above-ground temperatures can decrease leaf and embryonic tissues development (Bader et al 2007a, b;García-Núñez et al 2004;Weih and Karlsson 2001;Zimmerman 1983). We also found that aspect and slope might not limit radial growth.…”
Section: Discussionsupporting
confidence: 60%
“…Despite P. tarapacana possesses anatomical and physiological adaptations to tolerate and minimize frost damage, temperature constitutes a limiting factor because it affects many different processes involved in plant growth. Low soil temperatures can negatively influence root growth and nutrient uptake while low above-ground temperatures can decrease leaf and embryonic tissues development (Bader et al 2007a, b;García-Núñez et al 2004;Weih and Karlsson 2001;Zimmerman 1983). We also found that aspect and slope might not limit radial growth.…”
Section: Discussionsupporting
confidence: 60%
“…Bendix and Rafiqpoor (2001) also found relatively low mean soil temperature values (at 10 cm depth) in stands of P. incana and P. pauta at the treeline in Ecuador. In Bolivia, treelines formed by P. tarapacana grew at mean air temperature between 3.4 and 3.7°C (Rada et al 2001;Garcia-Nunez et al 2004) and values reported for the uppermost stands of P. sericea in Venezuela (Rada et al 1996) are also at the lower range of temperature values given by Körner (1998) and Körner and Paulsen (2004) for the tropical regions worldwide. These records suggest that treeline stands built by Polylepis trees seem to occur under specifically cold conditions.…”
Section: Discussionmentioning
confidence: 85%
“…According to general growth economy theory (Givnish 1984) the enlargement of the fine root system should reflect a compensation for water or nutrient deficiency. It was shown that high elevation forests can be exposed to severe drought at least periodically (James et al 1994;Lloyd and Fastie 2002;Li et al 2004), and those dry conditions have been reported for Polylepis treeline stands as well (Garcia-Nunez et al 2004;Morales et al 2004). However, water limitation is unlikely to be an important factor at our study transect in the humid eastern Andes cordillera.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Therefore, the Tibetan Plateau would likely be a preferred location for research on the photosynthetic performance of plants subjected to global climate change. To date, most research of the photosynthetic responses of alpine plants to changes in either CO 2 partial pressure or temperature has not been concentrated on the photosynthetic model parameters but rather on simple contrast analyses for photosynthetic measurements at extreme altitude (Cabrera et al, 1998;García-Núñez et al, 2004;Zhang et al, 2005;Sakata et al, 2007), especially on the Tibetan Plateau (Liu and Yang, 2001;Liu et al, 1999). Therefore, because Vc max and J max are two key parameters in the photosynthetic model (Farquhar et al, 1980), further research on these parameters should be conducted on plants of the Tibetan Plateau.…”
Section: Introductionmentioning
confidence: 99%